THE RELATIONSHIP BETWEEN PERSONALITY AND SOCIAL ENVIRONMENT WITH MORAL BEHAVIOR AMONG ADOLESCENTS - Fatimah - Ibda; Noor Azniza Binti Ishak; Mohd Azrin Bin Mohd. Nasir (Psikoislamedia : Jurnal Psikologi, 2023)
The moral behavior of adolescents develops through the integration of cognitive maturity, emotional maturity, and the social environment. Although personality characteristics and the social environment influence moral behavior, little is known about the relationship between personality, the social environment, and moral behavior. This study involved 175 respondents, aged 19-22 years, selected from three colleges in the city of Banda Aceh. The sample was gathered using purposive sampling techniques, with data collection conducted through personality questionnaires, social environment questionnaires, and moral behavior questionnaires. The research findings revealed that the correlation coefficient (r) between the studied variables was 0.537 or 53.7 percent, indicating a strong relationship between personality and the social environment with moral behavior. These findings underscore the significance of personality and the social environment in promoting moral behavior among adolescents.